2009
DOI: 10.1002/smj.801
|View full text |Cite
|
Sign up to set email alerts
|

Managing for stakeholders, stakeholder utility functions, and competitive advantage

Abstract: A firm that manages for stakeholders allocates more resources to satisfy the needs and demands of its legitimate stakeholders than would be necessary to simply retain their willful participation in the firm's productive activities. We explain why this sort of behavior unlocks additional potential for value creation, as well as the conditions that either facilitate or disrupt the value‐creation process. Firms that manage for stakeholders develop trusting relationships with them based on principles of distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
836
0
102

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 912 publications
(1,025 citation statements)
references
References 71 publications
9
836
0
102
Order By: Relevance
“…In this context, considering the co-existence of all the stakeholders involved and ensuring transparent communication between them does not only encourage increased efficiency but also proves a driver of motivation and confidence among and for all stakeholders, and whether contracted or volunteers (Parent & Séguin, 2007;Harrison et al, 2010;Walters & Tacon, 2010). Therefore, decision makers at any organization, but at this club in particular, should constantly strive to identify which stakeholders belong to the organization and which merit its greatest attention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, considering the co-existence of all the stakeholders involved and ensuring transparent communication between them does not only encourage increased efficiency but also proves a driver of motivation and confidence among and for all stakeholders, and whether contracted or volunteers (Parent & Séguin, 2007;Harrison et al, 2010;Walters & Tacon, 2010). Therefore, decision makers at any organization, but at this club in particular, should constantly strive to identify which stakeholders belong to the organization and which merit its greatest attention.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is subsequently adopted by several studies (Driscoll & Starik, 2004;Eesley & Lenox, 2006;Parent & Deephouse, 2007;Aaltonen et al, 2008;Mainardes et al, 2012). Power is defined as the stakeholder's capacity to influence the organization, with Harrison, Bosse & Phillips (2010) referring to the concept as the first criterion to prioritize when taking into account the factors influencing the organization's decisions and distribution of value. Legitimacy is defined by Mitchell et al (1997) as the generalized perception that the actions of any given organization are convenient, suitable or appropriate according to social definitions, norms, values and beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This further suggests the requirement for a definition to encompass a need for an organisation and its stakeholders to rely on one another for continual of both survival. In addition, this standpoint raises the issue of reciprocity among stakeholders, which involves stakeholders actively coming together in knowledge sharing and value creation activities (Harrison et al, 2010;Bosse et al, 2009). …”
Section: Who Is a Stakeholder?mentioning
confidence: 99%
“…The research study of Frooman (1999) contends that the model introduced by Freeman (1984) to explain that aspect showed that there is mutual independence in the organization to stakeholder relationship. Various researchers (Phillips, 2010;Dunkin, Savage and Ford, 2004) concur that stakeholder theory's core assumptions are explainable in six constructs. Firstly, organizations involve themselves in relationships with numerous groups, which either are influenced by or influence them.…”
Section: Stakeholder Theorymentioning
confidence: 99%